Pengaruh Nilai Koefisien Tanaman (Kc) Pada Tanaman Tomat Cherry (Solanum L.Var. Cerasiforme) Dengan Sistem Fertigasi Menggunakan Autopot Pada Beberapa Tinggi Media Tanam - Bafdal, Nurpilihan (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2021)
Planting media is a medium (means) for growing plants. The height of the planting medium is one of the factors that can affect the water needs of plants.The amount of plant water requirements obtained will have an impact on the coefficient value of cherry tomato plants. Besides minimizing the need for plant water to the optimum limit, it is also necessary to maximize crop yields so that the optimal Kc value can be obtained. Therefore, a further study is needed to explain the relationship between the height of the planting medium and the coefficient value of the plant, in order to obtain the appropriate Kc value. This study aims to 1) assess the value of the coefficient of planting on several heights of the planting medium, and 2) examine the differences in the value of the coefficient of plants on several heights of the growing media. This study used a descriptive method to determine the relationship between the height of the growing medium and the height of the planting medium 6, 10 and 15 cm to the coefficient value of cherry tomato plants with autopot. The results showed that the Kc value The Kc value at 6 cm media height was 0.05 in the initial phase, 0.05-062 in the dev phase, and 0.62 in the mid phase. at 10 cm media height was 0.05 in the initial phase, the dev phase was 0.05-0.49, and the mid phase was 0.49. while the height of the 15 cm planting medium was 0.05 in the initial phase, the dev phase was 0.05-0.49, and the mid phase was 0.49. These results are influenced by factors including planting media, ETc, and ETo.